KUALITAS HIDUP REMAJA YANG MENGALAMI DISMENORE DI SMK NEGERI 2 SUMEDANG - Nadya Puspita Dewi; Tetti Solehati; Nur Oktavia Hidayati (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Dysmenorrhea is a pain before or during the menstrual period. The impact of dysmenorrhea are the disruption on physical function, emotional, social and school activities and disruption of quality of life. The study purpose is to detect the quality of life of adolescents with dysmenorrhea.The research method was a quantitative descriptive with total sampling technique to 195 students which selected using dysmenorrhea screening. The data were collected using the pediatric quality of life 4.0 generic module (PedsQL) teens report in Indonesian version which the validity and reliability have been tested. Analysis of data has been done to find out the mean value in each dimension and frequency distribution. The results showed that the mean value of the quality of life of adolescents with dysmenorrhea in general was 62,04 ± 8,15 and 51,8% was in the low. The mean value in physical dimension was 49,36 ± 9,19, emotional dimension was 57,62 ± 13,16, social dimension was 86,38 ± 13,28, and in the school dimension was 62,41 ± 14,77. The quality of life in high categories were in the emotional dimension (60,0%), social dimension (64,1%), and school dimension (60,5%). Meanwhile, the quality of life in low category was in the physical dimension (57,4%). It showed that the quality of life of adolescents with dysmenorrhea in SMK Negeri 2 Sumedang were low. It was recommended to the school and the health office in Sumedang district to provide the reproductive health education, specifically about the prevention and the treatment of dysmenorrhea on adolescents.